Pengaruh Social Media Marketing Instagram @vidiosports dan Online Customer Review Terhadap Kepuasan Pelanggan Melalui Keputusan Pembelian Sebagai Variabel Intervening - Setiadi, R Rifqi Hendra; Madiawari, Putu Nina (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The development of technology has now extended to various aspects of life, including streaming services. In this digital era, technology and the internet significantly help people access various information and entertainment. One of the streaming service platforms widely used in Indonesia is Vidio. The purpose of this study is to determine the extent to which Instagram social media marketing @vidiosports and online customer reviews influence customer satisfaction through purchase decisions for Vidio streaming service users. This research employs a quantitative method with a survey approach. Data were collected through questionnaires distributed to 100 respondents. The analysis uses non-probability sampling with purposive sampling techniques. Data analysis was conducted using Structural Equation Modeling (SEM) techniques with SmartPLS 3.2.9 software. The results of this study are that social media marketing does not significantly influence customer satisfaction, online customer reviews do not significantly influence customer satisfaction, social media marketing significantly influences purchase decisions, online customer reviews significantly influence purchase decisions, purchase decisions significantly influence customer satisfaction, social media marketing significantly influences customer satisfaction through purchase decisions, and online customer reviews significantly influence customer satisfaction through purchase decisions. Suggestions for Vidio include enhancing Instagram social media marketing @vidiosports by being engaging and consistent in obtaining good online customer reviews.